Treni della felicità. Społeczna inicjatywa na rzecz dzieci w powojennych Włoszech (Politeja, 2022)
TRENI DELLA FELICITÀ: A SOCIAL INITIATIVE FOR CHILDREN IN POST-WAR ITALYThis paper is devoted to the analysis of the origins and development of a social initiative, the so-called Treni della felicità (Trains of happiness) and its impact on shaping civil society and sense of national community in the post-war Italy. This project, initiated by the Union of Italian Women (Unione Donne Italiane, UDI) and then promoted mainly by the Italian Communist Party (Partito Comunista Italiano, PCI) assumed the transfer of tens of thousands of children from families in need from southern Italy to relatively more developed north-central regions of the country in order to provide them better living conditions after World War II. This example of the fight against poverty and inequalities seems to be a forgotten symbol of solidarity and renewal of the idea of civil society in post-totalitarian Italy. Moreover, this action for children is not only an example of civic activity, but also an important element in the debate on the traditional division of Italy into North and South.